Production inefficiency in water treatment at the Barekese headworks in Ghana - Darko, Vincent Opoku Ware (2016)
Thesis submitted to The Department of Economics of The College of Humanities and Social Sciences, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement for award of Master of Science in Energy and Resource Economics.